Embodied Engagements: Body Mapping in a Sociology of Sexuality Classroom. (July 2021) - Fields, Jessica; Johnson, Stephanie; MacFife, Bex; Roach, Patricia; steinfeld, era
Using a collaborative autoethnographic approach, we discuss body mapping as an embodied pedagogical practice for teaching sexuality. Body mapping centers stigmatized bodies through guided visual, oral, and textual self-representation. We begin by discussing embodied pedagogies and the bind of representation (ideas grounded in the work of feminists of color) in teaching and learning about sexuality. We then consider three body mapping experiences: in a sexuality education graduate seminar ( seminar mapping ), as a remote synchronous practice ( remote mapping ), and as a solo practice ( solo mapping ). We explore challenges in representation, embodied difference, and the im/possibility of mapping the sexual. Finally, we consider the implications and applications of body-mapping exercises for sexualities classrooms.